SEED LONGEVITY AND CRYOBIOTECHNOLOGY IN THE ORCHID GENUS Cattleya - Fileti, Jessica Fontes (2021)
BACKGROUND: Orchid seeds are reputed to be relatively short-lived, although comparative studies across a wide range of storage temperatures and moisture contents are few. OBJECTIVE: To explore how a wide range of temperature and moisture contents affects seed longevity in the orchid genus Cattleya. MATERIALS AND METHODS: Seeds of three Brazilian orchid species in the genus Cattleya (C. amethystoglossa, C. kautskyana and C. tigrina) were subjected to controlled deterioration (CD) and seeds at three moisture levels were stored for up to 270 days at temperatures as low as -196 degrees C. Seed ageing curves were constructed and seed quality assessed as germination level and speed index in vitro, and by tetrazolium staining. Seed morphometry, lipid content and composition were also determined. RESULTS: Seeds were found to be lipid rich (54-70% DW) and short-lived under CD, with P(50)s varying less than two-fold (42 to 69 h) at 41 degrees C. At cold (5 degrees C) to ultracold (-196 degrees C) temperatures longevity was greatest after pre-drying seeds to 15% RH, with germination varying by c. 6% after 270 days storage at these temperature limits. However, storage at -20 degrees C resulted in a 5-46% reduction in germination, indicating a dry-seed sensitivity to conventional seed bank temperature. Ultra-dry (silica gel) and high humidity (82% RH) storage, in combination with various temperatures, compromised viability in one or more species. Overall, seed longevity in C. kautskyana > C. tigrina > C. amethystoglossa, which also reflected the pattern of embryo volume. The prospect that the generally shorter lifespans in orchid seeds may relate to stochastic processes the negative impact of which reach criticality sooner in smaller embryos requires further testing. CONCLUSION: Further evidence is provided that cryobiotechnology provides a biobanking option for orchid seeds with relatively short lifespans.